An algorithm for the estimation of gestational age at the time of fetal death. - Conway DL; Hansen NI; Dudley DJ; Parker CB; Reddy UM; Silver RM; Bukowski R; Pinar H; Stoll BJ; Varner MW; Saade GR; Hogue C; et al. (Paediatric & Perinatal Epidemiology, 2013)
Background: Accurate assignment of gestational age (GA) at time of fetal death is important for research and clinical practice. An algorithm to estimate GA at fetal death was developed and evaluated.Methods: The algorithm developed by the Stillbirth Collaborative Research Network (SCRN) incorporated clinical and post-mortem data. The SCRN conducted a population-based case-control study of women with stillbirths and livebirths from 2006 to 2008 in five geographical catchment areas. Rules were developed to estimate a due date, identify an interval during which death likely occurred, and estimate GA at the time of fetal death. Reliability of using fetal foot length to estimate GA at death was assessed.Results: The due date estimated for 620 singleton stillbirths studied was considered clinically reliable for 87%. Only 25.2% of stillbirths were documented alive within 2 days before diagnosis and 47.6% within 1 week of diagnosis. The algorithm-derived estimate of GA at time of fetal death was one or more weeks earlier than the GA at delivery for 43.5% of stillbirths. GA estimated from fetal foot length agreed with GA by algorithm within 2 weeks for 75% within a subset of well-dated stillbirths.Conclusions: Precise assignment of GA at death, defined as reliable dating criteria and a short interval (≤1 week) during which fetal death was known to have occurred, was possible in 46.6% of cases. Fetal foot length is a relatively accurate measure of GA at death and should be collected in all stillbirth cases.